Inadequate dietary phosphorus levels cause skeletal anomalies and alter osteocalcin gene expression in Zebrafish - Costa, Juliana M. [UNESP]; Sartori, Maria M. P. [UNESP]; Do Nascimento, Nivaldo F. [UNESP]; Kadri, Samir M. [UNESP]; Ribolla, Paulo E. M. [UNESP]; Pinhal, Danillo [UNESP]; Pezzato, Luiz E. [UNESP] (MDPI, 2018)
Phosphorus (P) is an essential mineral for the development and maintenance of the vertebrate skeletal system. Modulation of P levels is believed to influence metabolism and the physiological responses of gene expression. In this study, we investigated the influence of dietary P on skeletal deformities and osteocalcin gene expression in zebrafish (Danio rerio), and sought to determine appropriate levels in a diet. We analyzed a total of 450 zebrafish within 31 days of hatching. Animals were distributed in a completely randomized experimental design that consisted of five replications. After an eight-week experiment, fish were diaphanized to evaluate cranial and spinal bone deformities. Increases in dietary phosphorus were inversely proportional to the occurrence of partial spine fusions, the absence of spine fusions, absence of parallelism between spines, intervertebral spacing, vertebral compression, scoliosis, lordosis, ankylosis, fin caudal insertion, and craniofacial deformities. Additionally, osteocalcin expression was inversely correlated to P levels, suggesting a physiological recovery response for bone mineralization deficiency. Our data showed that dietary P concentration was a critical factor in the occurrence of zebrafish skeletal abnormalities. We concluded that 1.55% P in the diet significantly reduces the appearance of skeletal deformities and favors adequate bone mineralization through the adjustment of osteocalcin expression.
Keywords: Abnormalities; Bone mineralization; Osteocalcin